Web-Based Mail Search Using the Levenshtein Distance Algorithm - Mayora Lolly Ishimora; Herlawati Herlawati; Sri Rejeki (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2022)
The use of information technology in filing letters has been widely applied, especially in government institutions. In the Administrative Affairs of the Police Information Technology Bureau, the archiving of incoming and outgoing letters is still done manually, by utilizing records in a large agenda book and stored in a large folder. The absence of a system capable of assisting mail processing causes work to be inefficient, especially in terms of searching for letters. The purpose of this research is to produce a website that can help search letters by applying the Levenshtein Distance Algorithm. The design begins with needs analysis, design, implementation, verification (system testing), operation and maintenance. A website that can search letters by applying the Levenshtein Distance Algorithm was generated. This website is very helpful in the process of searching for letters to the Administrative Affairs of the Police Information Technology Bureau.